Analisis Potensi dan Pengembangan Pariwisata Berbasis Masyarakat di Desa Tulakadi Kawasan Perbatasan Indonesia - Yudha Eka Nugraha (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
This study aims to identify potential natural, cultural, and artificial tourist attractions in the border area of Tulakadi Rural area, East Nusa Tenggara. Another objective to be achieved in this research is to determine and develop community-based tourism, Tulakadi Village based on a community approach. The method in this research uses descriptive qualitative types for analysis, exploration of tourism potential and tourism development according to community needs. The data technique was carried out through structured interviews and focus group discussions with residents and village officials. The results of this study show that Tulakadi Village has various tourist destination in the border area, especially culture-based such as Sakurai dances, weaving woven with natural colouring, natural landscapes of Alor Island, and artificial attraction, namely PLBN Mota’ain and Man-Made attraction of Asam Jokowi site. Based on the community and the development of a community-based tourism approach, efforts are made through the interaction of stakeholders such as the government, academics through socialization and training for awareness of tourism for the community, and orders from community groups including tourism awareness groups to develop tourism in Tulakadi Village